The synaptonemal complex stabilizes meiosis in allotetraploid Brassica napus and autotetraploid Arabidopsis thaliana - Zhang, Yashi (The New phytologist, 2025)
© 2025 The Author(s). New Phytologist © 2025 New Phytologist Foundation.